2018
DOI: 10.1177/1369433218773132
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric compressive behavior of recycled aggregate concrete columns after freezing and thawing cycles

Abstract: The eccentric compressive behavior of 18 recycled aggregate concrete columns after freezing and thawing cycles were investigated. The effect of the number of freezing and thawing cycles, the replacement ratio of recycled coarse aggregate, and the eccentricity of axial loading on the eccentric compressive behavior of columns was analyzed. The results show that the strain distribution along the depth of cross section of columns was plane during the eccentric compression test after freezing and thawing cycles. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Hence, recycled aggregate concrete (RCA) may demonstrate less response to external loads. This has been attributed to RCA's lower strength and higher porosity compared to natural coarse aggregate (NCA), as indicated by [24]. In the initial stages of loading, the load-displacement curve of RCA concrete with varying contents of RCA (25%, 50%, and 100%) showed a nearly linear correlation between the applied load and displacement, which denotes elastic deformation of the slender columns.…”
Section: Load-displacement and Load-strain Relationshipmentioning
confidence: 99%
“…Hence, recycled aggregate concrete (RCA) may demonstrate less response to external loads. This has been attributed to RCA's lower strength and higher porosity compared to natural coarse aggregate (NCA), as indicated by [24]. In the initial stages of loading, the load-displacement curve of RCA concrete with varying contents of RCA (25%, 50%, and 100%) showed a nearly linear correlation between the applied load and displacement, which denotes elastic deformation of the slender columns.…”
Section: Load-displacement and Load-strain Relationshipmentioning
confidence: 99%
“…The freeze-thaw cycle tests indicated the recycled concrete aggregate can deteriorate the freeze-thaw resistance of concrete [47][48][49]. When exposed to freeze-thaw cycles, its inappropriate freeze-thaw resistance can further deteriorate its loading capacity [50], compressive performance [51], seismic performance [52] and cyclic mechanical performance loading capacity [53]. The further study by Salem et al indicated the recycled concrete aggregate can achieve similar freeze-thaw resistance to normal aggregate under proper air-entraining [54].…”
Section: Introductionmentioning
confidence: 99%
“…As for Recycle, this concept is fully embodied in those applications adopting recycled aggregate concrete (RAC). In the past few decades, sufficient experimental studies have been carried out for RAC in terms of material properties (Sagoe-Crentsil et al, 2001;Tabsh and Abdelfatah, 2009;Xiao et al, 2005), component properties (Choi and Yun, 2012;Etxeberria et al, 2007;Gonza´lez-Fonteboa and Martı´nez-Abella, 2007;Seara-Paz et al, 2018;Wardeh and Ghorbel, 2019;Xiao et al, 2014a: 692-712;Yan et al, 2018), structural properties (Liu et al, 2020;Xiao et al, 2014bXiao et al, : 1381Xiao et al, -1405 and the bonding properties with reinforcement (Prince and Singh, 2013;Xiao and Falkner, 2007). Some studies also analyzed the effect of RAC on the frame beam-column joint, which is essential to the safety and integrity of recycled concrete frame structure (Corinaldesi et al, 2011;Hu and Kundu, 2019;Letelier Gonzalez and Moriconi, 2014;Xue et al, 2018).…”
Section: Introductionmentioning
confidence: 99%